Characterization of clinical human prostate cancer lesions using 3.0‐T sodium MRI registered to Gleason‐graded whole‐mount histopathology. Issue 5 (14th November 2018) - Broeke, Nolan C.; Peterson, Justin; Lee, Joseph; Martin, Peter R.; Farag, Adam; Gomez, Jose A.; Moussa, Madeleine; Gaed, Mena; Chin, Joseph; Pautler, Stephen E.; Ward, Aaron; Bauman, Glenn; et al.
Abstract : Background: Overtreatment of prostate cancer (PCa) is a healthcare issue. Development of noninvasive imaging tools for improved characterization of prostate lesions might reduce overtreatment. Purpose: To measure the distribution of tissue sodium concentration (TSC), proton T2 ‐weighted signal, and apparent diffusion coefficient (ADC) values in human PCa and to test the presence of a correlation between regional differences in imaging metrics and the Gleason grade of lesions determined from histopathology. Study Type: Cross‐sectional. Subjects: Ten men with biopsy‐proven PCa. Sequences/Field Strength: Sodium, proton T2 ‐weighted, and diffusion‐weighted MRI data were acquired using Broad‐Band 3D‐Fast‐Gradient‐Recalled, 3D Cube (Isotropic 3D‐Fast‐Turbo‐Spin‐Echo acquisition) and 2D Spin‐Echo sequences, respectively, with a 3.0T MR scanner. Assessment: All imaging data were coregistered to Gleason‐graded postprostatectomy histology, as the standard for prostate cancer lesion characterization. Regional TSC and T2 data were assessed using percent changes from healthy tissue of the same patient (denoted ΔTSC, ΔT2 ). Statistics: Differences in ΔTSC, ADC, and ΔT2 as a function of Gleason score were analyzed for each imaging contrast using a one‐way analysis of variance or a nonparametric t ‐test. Correlations between imaging data measures and Gleason score were assessed using a Spearman's ranked correlation. Results: Evaluation of the correlation of ΔTSC, ADC, and ΔT2 datasets with Gleason scoring revealed that only the correlation between ΔTSC and Gleason score was statistically significant ( r s = 0.791, p < 0.01), whereas the correlations of ADC and ΔT2 with Gleason score were not ( r s = –0.306, p = 0.079 and r s = –0.069, p = 0.699, respectively). In addition, all individual patients showed monotonically increasing ΔTSC with Gleason score. Data Conclusion: The results of this preliminary study suggest that changes in TSC, assessed by sodium MRI, has utility as a noninvasive imaging assay to accurately characterize PCa lesions. Sodium MRI may provide useful complementary information on mpMRI, which may assist the decision‐making of men choosing either active surveillance or treatment. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:1409–1419.